Involvement of TRPV1 Channels in Energy Homeostasis - Christie, Stewart; Wittert, Gary A.; Li, Hui; Page, Amanda J. (Frontiers in Endocrinology, 2018)
The ion channel TRPV1 is involved in a wide range of processes including nociception, thermosensation and, more recently discovered, energy homeostasis. Tightly controlling energy homeostasis is important to maintain a healthy body weight, or to aid in weight loss by expending more energy than energy intake. TRPV1 may be involved in energy homeostasis both in the control of food intake and energy expenditure and therefore maybe a potential therapeutic target for the treatment of obesity.